Murder party [videorecording (Blu-Ray)] - Sharp, Chris; Sharp, Chris; Barnett, Sandy; Blair, Macon; Goldblatt, Paul; Lacey, William; Rock, Stacy; Rock, Stacy; Saulner, Skei; Tangradi, Bill; Sia, Beau; Saulnier, Jeremy; et al. (Everybody Dies Inc., 2007)
"A random invitation to a Halloween party leads a man into the hands of a rogue collective intent on murdering him for the sake of their art, sparking a bloodbath of mishap, mayhem and hilarity."--IMDb.